IMPLEMENTATION OF THE ZONING SYSTEM AS A SELECTION METHOD FOR HIGH SCHOOL ENTRANCE IN RELATION TO SCHOOL DISTRIBUTION - Riyan Ardiansyah, Feri Arensyi (EDUCATIONE, 2025)
Education is a fundamental pillar of national development, and equitable access to education is crucial for achieving educational equality. In Indonesia, the government has implemented a zoning system as a selection mechanism for State Senior High School admissions. This system prioritizes students based on the proximity of their residence to the school. However, disparities in the distribution of high schools across various regions pose significant challenges to the effectiveness of this policy. This study aims to analyze the effectiveness of the zoning system in Pasuruan Regency, East Java, by examining the distribution of high schools and its impact on students’ access to education. Using a descriptive quantitative approach, data on the number and location of high schools were obtained from the official website of the Ministry of Education and Culture. The findings reveal that the zoning system is less effective in areas where the distribution of high schools is uneven. Many sub-districts lack adequate school facilities, forcing students to travel long distances or enroll in schools outside their zones, often facing admission barriers due to the zoning policy. As a result, students from underserved areas experience limited educational opportunities, further exacerbating educational inequality. To improve the effectiveness of the zoning system, the government should prioritize the equitable distribution of high school facilities before fully enforcing the policy. Strengthening infrastructure in underserved regions will enhance access to quality education and ensure a more inclusive and fair educational system.